Therapeutic principles in healing reliability of addictive substances and behavioral disorders - Saifuddin, Ahmad (Indigenous, 2021)
Healing mental and behavioral disorders can be done with a variety of approaches, one of which is a religious approach. It was carried out at the inabah in Sirnarasa. This study aims to uncover the therapeutic principles contained in religious therapies to cure mental and behavioral disorders, such as addiction and avoidance behavior. The approach used is qualitative, while the research method is case study. Data was collected by interviewing the person in charge of religious therapy in Sirabah Village and two students who had recovered. In addition, it also uses documentation of therapy manuals. The result, inabah therapy which includes various kinds of prayers, repentance bathing, and remembrance contains several therapeutic principles, namely water therapy; catharsis; increased awareness of self orientation, time and place; changing irrational beliefs into rational; unconditional positive regard. In addition, therapy in Inabah also includes psychoeducation encouragement to the community and parents of students about the importance of parenting, giving examples, and environmental modification.Keywords:healing; inabah therapy; religious approach; therapeutic principles.healing; inabah therapy; religious approach; therapeutic principles